Annealing Temperature Effect on Structural and Luminescence Spectroscopy of Y2SiO5:Ce3+ Nanomaterial Synthesized by Sol–Gel Method - Hamroun, M.S.E.; Guenanou, A.; Guerbous, L.; Chebout, R.; Bachari, K. (Journal of Research Updates in Polymer Science, 2022)
Ce3+ - doped Y2SiO5 nanophosphors were successfully produced by Sol-Gel process. To study the influence of the temperature on the structure and the luminescence of Y2SiO5:Ce3+, we annealed the xerogels at the temperatures 800, 900, 950, 1000, 1050 and 1250 °C. The X-ray diffraction technique (XRD), field emission scanning electron microscopy (FEG-SEM), Fourier transform infrared spectroscopy (FTIR) and steady photoluminescence were used to characterize the samples. The crystallite size keeps the same value in the temperature range 950-1050 °C. The room temperature steady photoluminescence emission and excitation of Ce3+ in X1-Y2SiO5:Ce3+ nanomaterial with increasing temperature were measured and investigated. At the crystallization temperature of 1250 °C, we have a new structure X2- Y2SiO5:Ce3+ with grain sizes larger than the X1-Y2SiO5:Ce3+ and also intense violet-blue emission.